COVID-19 Vaccine Uptake in Pakistan: No Time to Err - Sarosh Saleem (Journal of Shalamar Medical & Dental College, 2021)
COVID 19 pandemic has had a significant impact on social, physical, mental and financial aspects of human life. Among the sickness and despair experienced for last more than a year, COVID vaccination is a ray of hope. The uptake of COVID vaccines has remained low. The government, institutions as well healthcare professionals should take this responsibility of promoting vaccination. A strong will and simple nudges are what it takes to fight the menace of the COVID pandemic.